To Internationalize Rapidly from Inception: Crowdsource - Nirosh Kannangara; Mohsen Akhavannia; Elnaz Heidari (Technology Innovation Management Review, 2012)
Technology entrepreneurs continuously search for tools to accelerate the internationalization of their startups. For the purpose of internationalizing rapidly from inception, we propose that technology startups use crowdsourcing to internalize the tacit knowledge embodied in members of a crowd distributed across various geographies. For example, a technology startup can outsource to a large crowd the definition of a customer problem that occurs across various geographies, the development of the best solution to the problem, and the identification of attractive business expansion opportunities. In this article, we analyze how three small firms use crowdsourcing, discuss the benefits of crowdsourcing, and offer six recommendations to technology entrepreneurs interested in using crowdsourcing to rapidly internationalize their startups from inception.